Use of the let it pass strategy among ASEAN English speakers - Myintzu Winn (2021)
This study focuses on the use of the let it pass strategy (Firth, 1996) by English speakers from five member countries of the Association of Southeast Asian Nations (ASEAN) during interaction with each other. The data was from the video recordings of the participants during their conversations. Close and indepth analyses were carried out on instances of let it pass used by them. Then, retrospective interviews were conducted with each participant. Results showed that let it pass was a communication strategy the participants used to make their conversation flow smoothly, and that they used it as long as their nonunderstanding of what their interlocutor was saying did not cause a communication breakdown between them. This finding leads to the conclusion that the use of let it pass systematically facilitates talk when English speakers from ASEAN countries communicate with each other in English. Implications are noted for English language teaching and further research.